Service requirement for terminal delivery: An empirical study from the perspective of online shoppers - Junjie Xu; Ling Jiang; Yiliang Li (Journal of Industrial Engineering and Management (JIEM), 2013)
To investigate customer's service requirement for parcel delivery, combining with theoretical analysis and empirical test, a measuring model of customer service requirement was proposed for terminal delivery. Based on literature reviews, five potential dimensions with 27 items were initially discussed. Through exploratory factor analysis on samples collected from Taobao networks, four dimensions with 18 measurement items were finally confirmed including service attitude, service reliability, service standardization and service flexibility. By further confirmatory factor analysis, the fitness of this measuring model was proved to be acceptable. The research revealed that online shoppers paid attention to not only service result but also service process, so related suggestions were also proposed for express firms to promote their service management.
Keywords: 650; terminal delivery; service requirement; logistics service quality; delivery management